Gel polymer electrolyte for reversible metal electrodeposition dynamic windows enables dual-working electrodes for faster switching and reflectivity control - Cai, Yuchun; Hernandez, Tyler S.; Yeang, Andrew L.; Strand, Michael T.; Yavitt, F. Max; Abraham, Eldho; McGehee, Michael D. (Frontiers in Nanotechnology, 2022)
Dynamic windows based on reversible metal electrodeposition are an attractive way to enhance the energy efficiency of buildings and show great commercial potential. When a liquid electrolyte is used to build dynamic windows, there is a risk for the two electrodes to touch and cause short-circuiting, especially in larger-scale formats. Here we developed a poly (vinyl alcohol) (PVA) gel polymer electrolyte (GPE) with 85 % transmittance that is sufficiently stiff to act as a separator. The GPE is implemented into windows that exhibit comparable electrochemical and optical properties to windows using a liquid electrolyte. Furthermore, the GPE enables the fabrication of windows with dual-working electrodes (WE) and a metal mesh counter electrode in the center without short-circuiting. Our dual-WE PVA GPE window reaches the 0.1% transmittance state in 101 s, more than twice the speed of liquid windows with one working electrode (207 s). Additionally, each side of the dual-WE GPE window can be tinted individually to demonstrate varied optical effects (i.e., more reflective, or more absorptive), providing users and intelligent building systems with greater control over the appearance and performance of the windows in a single device architecture.